Accountability mechanisms of inquiries and investigations into Australian governments' responses to the COVID‐19 pandemic. (26th May 2022) - Rajan, Rachana; Topp, Stephanie M.
Abstract: Objective: Australian federal, state and territory government responses to the COVID‐19 pandemic have been subject to public oversight by various domestic inquiries and investigations, despite little analysis about what accountability these processes deliver in the context of public health emergencies (PHEs) involving communicable disease. This article identifies and describes recent inquiries and investigations. It examines their ability to promote accountability through mechanisms of answerability (information and justification) and enforceability (sanctions). Methods: A systematic scoping review was used to identify inquiries and investigations initiated by May 2021 and to examine the answerability and enforceability mechanisms present. Three diverse case studies were chosen for further description and examination. Results: Seven parliamentary inquiries, two commissions/boards of inquiry and one Ombudsman investigation were identified. All had numerous mechanisms of answerability. All but two embedded enforceability mechanisms; these were limited, however, to basic reporting. Conclusion: While inquiries and investigations can promote accountability through various mechanisms of answerability, external enforceability mechanisms may be beneficial to strengthen accountability and ensure learning. Implications for public health: Consideration of the kind of accountability that public inquiries and investigations should provide in the context of communicable disease PHEs, and how accountability mechanisms can be strengthened, may improve future public health responses.